Susceptibility Pattern of Bacteria Isolated from Patients Admitted in Medical ICU with Pneumonia - Rifat Yasmin, Lubna Ghazal, Syeda Turab Fatima Abidi, Tazaeen Hina Kazmi, Huma Hussain, Muhammad Fareed Azam (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Patients in ICU presenting with severe disease suffer from multidrug-resistant bacteria, resuting in reduced therapeutic options which cover ICU pathogens spectrum. Identification of causative organism and its antibiotics sensitivity pattern has become cornerstone for antibiotic selection. β-Lactams i.e. cephalosporins, carbapenems, penicillins, and monobactams constitute 60% of total antibacterials used, however; with high usage of such antibiotics the emergence of resistance. Aim: To determine prevalence of local type of bacterial isolates and their antibiotic susceptibility. Study Design: Cross sectional study Place and Duration of Study: Medical ICU, Pakistan Ordinance Factories Hospital, Wah Cantt from 1st January 2020 till 31st July 2021. Methodology: One hundred patients were enrolled. Samples were taken from blood, sputum, bronchoalveolar lavage and tracheal secretions of the patient and sent to microbiologist for culture and sensitivity reports. Results: The mean age was 57.52+13.427 years, 47 females and 53 male patients. 72 patients were shifted out and remaining 28 died. In 57 patients, sputum specimen was taken, blood specimen of 24 patients, tracheal secretion of 8 patients and 11 patients bronchoalveolar lavage was taken. 33 were positive for Klebsiella pneumoniae, 29 patients were positive for acinetobacter baumanii. Pseudomonas aeuriginosa was positive in 18 patients, 05 patients for E. coli. In gram positive category; 05 patients were positive for staph aureus, 06 patients for MRCONS, 3 to MRSA and 1 patient for coagulase negative staphylococcus species. Conclusion: The high levels of antibiotic resistance are seen among both gram negative and gram positive isolates. Presence of elevated resistance to multiple drugs is an indicator for high prevalence of multi-drug resistant gram positive as well as gram negative organisms, so proper identification of organism in order to ascertain administration of emperical drugs most effective against the isolated organism is recommended in severe cases. Keywords: Antibiogram, Bacterial isolate, Pneumonia, Sensitivity